Leveraging Remote Work Services in Libraries: Building Community and Strengthening the Local Economy - Sessions, Savannah (Maine Policy Review, 2024)
This article explores the preliminary findings of the first year of the Remote Work Through Libraries Initiative, a three-year project investigating how libraries’ remote work services impact community and economic vitality. The COVID-19 pandemic catalyzed a significant shift in work habits, prompting libraries to continue evolving beyond information repositories to dynamic hubs, now offering tailored services to remote workers, thereby fostering community cohesion and bolstering local economies. Remote work support is a nascent frontier for library services, with limited existing research. A novel initiative led by the Maine State Library, in partnership with the Department of Economic and Community Development, allocated over $1.7 million in American Rescue Plan Act funds to 39 public libraries. This endeavor, aligned with Governor Mills’ economic development plan, will fortify libraries with tools needed to attract and assist remote workers, including updated physical spaces and technologies to accommodate workers' needs. References: The Pew Charitable Trusts. (2020, October 7). American democracy can be found at the library. https://www.pewtrusts.org/en/research-and-analysis/articles/2020/10/07/american-democracy-can-be-found-at-the-library
Keywords: Remote Work; ARPA funds; Remote work Public libraries; Community engagement; Economic development; Workforce support